Peran Terapi Akupunktur pada Nyeri Tulang Metastasis - MIHARDJA, HASAN; AGUNG, ZULHAFIZ MUFTI (Indonesian Journal of Cancer, 2016)
ABSTRACTBone pain caused by cancer is a common complication in bone metastasis. Bone pain has the characteristic triad of pain including continuous pain, spontaneous pain and incident pain. Various mechanisms that allow bone metastasis can cause pain have been reported. These mechanisms include the possibility of local production of growth factors and cytokines. The management of the pain bone metastasis include aspects of pharmacological and non-pharmacological therapies. Acupuncture can play a role in the treatment of bone metastasis pain through modulation of various neurotransmitters and increase the production of endogenous opioids that can cause analgesika effect. This paper describes a male patient aged 62 years old with painful bone metastasis who experience an improvement after acupuncture therapy, with the goal of providing information on the possible use of acupuncture for painful bone metastasis.Â ABSTRAKNyeri tulang yang disebabkan oleh kanker merupakan suatu komplikasi yang sering terjadi pada metastasis tulang. Nyeri tulang ini memiliki karakteristik trias nyeri, yaitu nyeri terus-menerus, nyeri spontan, dan nyeri insiden. Berbagai mekanisme yang memungkinkan metastasis tulang dapat menyebabkan rasa nyeri telah dilaporkan. Mekanisme ini termasuk kemungkinan adanya produksi lokal faktor pertumbuhan dan sitokin. Tata laksana pada nyeri tulang metastasis meliputi aspek terapi farmakologis dan nonfarmakologis. Akupunktur dapat berperan dalam terapi nyeri tulang metastasis melalui modulasi berbagai neurotransmitter dan meningkatkan pengeluaran endogen opioid sehingga menimbulkan efek analgesik. Makalah ini memaparkan pasien laki-laki berusia 62 tahun dengan nyeri tulang metastasis yang mengalami perbaikan setelah terapi akupunktur, dengan tujuan memberikan informasi kemungkinan penggunaan akupunktur pada nyeri metastasis tulang.